(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Colonial Assam witnessed the rise of linguistic nationalism as a dominant force developing identity and political mobilization. This study examines maturation process of linguistic nationalism in Assam during the colonial period, centering on how colonial policies shaped language based identity creation and political ambitions. Depending on historical interpretation and examining archival records and literary texts, the paper studies the antagonism between Bengali and Assamese in terms of territorial and cultural contentions. It also emphasizes the missionary engagement, the emergence of middle class, Bengali Assamese linguistic disputes, population diversity and regional programs for education. The conclusions disclose that linguistic nationalism in Assam both a reply to colonial linguistic structure and a push for colonial reorganizations. The study emphasizes the lasting impact of colonial linguistic strategies on Indian nation building and emphasizes the language complexity in the local politics of later post-colonial Assam.